2018
DOI: 10.1038/s41398-018-0244-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective efficacy of P7C3 compounds in primate hippocampus

Abstract: There is a critical need for translating basic science discoveries into new therapeutics for patients suffering from difficult to treat neuropsychiatric and neurodegenerative conditions. Previously, a target-agnostic in vivo screen in mice identified P7C3 aminopropyl carbazole as capable of enhancing the net magnitude of postnatal neurogenesis by protecting young neurons from death. Subsequently, neuroprotective efficacy of P7C3 compounds in a broad spectrum of preclinical rodent models has also been observed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 94 publications
0
28
0
Order By: Relevance
“…It has been demonstrated that P7C3 and its analogs have neuroprotective efficacy in a broad range of preclinical rodent and nonhuman primate models relying on the activation of NAMPT. 635 638 Therefore, the neuroprotective activity of P7C3 offers a new pharmacotherapy for age-associated ALS, Alzheimer’s disease and Parkinson’s disease. 635 , 637 , 638 SBI-797812 activates NAMPT via stabilizing the NAMPT phosphorylation at His247, enhancing the efficiency of NMN generation, providing another option to raise NAD + .…”
Section: Boosting Nad + As a Therapeutic Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that P7C3 and its analogs have neuroprotective efficacy in a broad range of preclinical rodent and nonhuman primate models relying on the activation of NAMPT. 635 638 Therefore, the neuroprotective activity of P7C3 offers a new pharmacotherapy for age-associated ALS, Alzheimer’s disease and Parkinson’s disease. 635 , 637 , 638 SBI-797812 activates NAMPT via stabilizing the NAMPT phosphorylation at His247, enhancing the efficiency of NMN generation, providing another option to raise NAD + .…”
Section: Boosting Nad + As a Therapeutic Strategymentioning
confidence: 99%
“… 635 638 Therefore, the neuroprotective activity of P7C3 offers a new pharmacotherapy for age-associated ALS, Alzheimer’s disease and Parkinson’s disease. 635 , 637 , 638 SBI-797812 activates NAMPT via stabilizing the NAMPT phosphorylation at His247, enhancing the efficiency of NMN generation, providing another option to raise NAD + . 639 Together, the NAMPT enhancers, P7C3 and SBI-797812, warrant further study for the clinical treatment of neuron related diseases.…”
Section: Boosting Nad + As a Therapeutic Strategymentioning
confidence: 99%
“…Mice were then administered either vehicle (TBI-Veh, Sham-Veh) or P7C3-A20 (10 mg⋅kg −1 ⋅day −1 intraperitoneally [IP]; TBI-P7C3-A20) for 4 wk. P7C3-A20 is an aminopropyl carbazole that elevates cellular nicotinamide adenine dinucleotide, enhances survival of adult-born young hippocampal neurons, and has been shown to preserve mature neurons and improve cognition in various models of nervous system disease and injury ( 25 45 ). Immediately after treatment completion, cognitive function in the 15-mo-old animals was evaluated through Morris water maze (MWM) testing.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore adopted a neurogenic approach that is more translatable to human conditions, and provide support for the emerging role of neurogenesis in DG inhibition. Neurogenic therapies, such as exercise, MEM or other compounds such as P7C3 (which has recently been validated in nonhuman primates [71]) could therefore be viable approaches for treating cognitive and mental health disorders that are associated with altered excitationinhibition balance in the DG.…”
Section: Resultsmentioning
confidence: 99%